Business Model Innovation through the Expansion of Digital Platforms - Seyed Hamed Vares; Nastaran Haji Heydari; Mohammad Kargar Shouraki; Morteza Hadizadeh (‫مدیریت بازرگانی)
Objective This study aims to identify and analyze the role of digital platforms in improving business processes, data management, and communications. It thoroughly examines the direct and indirect impacts of digital platforms on organizational structures and business performance to find how digital technologies can facilitate innovation and contribute to the development of new business models development. It also seeks to explore the challenges and opportunities they present for organizations. Focusing on a specific digital framework, this study investigates how digital platforms are utilized at different organizational levels to enhance productivity and efficiency in work processes. Additionally, it tries to comprehend how organizations can benefit from the innovative opportunities created by advancements in digital technology, emphasizing how these opportunities can be leveraged to improve customer interactions and marketing strategies.